Aggregation-induced demulsification technology for the separation of highly emulsified oily wastewater produced in the petrochemical industry. (10th November 2022) - Ma, Fu-Xin; Hao, Bin; Xi, Xiong-Yu; Wang, Rui; Ma, Peng-Cheng
Abstract: To improve the resource utilization of oily wastewater emulsion produced in the petrochemical industry, an aggregation-induced demulsification (AID) technology, consisting of multi-stage packed beds filled with polyurethane sponge in a gradient configuration mode, was developed in this study. Based on the verification on the technical principle of AID, an industrial-scale setup was performed, targeting on removing highly emulsified oil in wastewater. The results showed that when the inlet pressure was 0.2–0.4 MPa and average temperature of raw water was 35 °C, the chemical oxygen demand (COD) in the emulsion was reduced from 3000-12450 mg/L to below 500 mg/L with simultaneous recovery of emulsified oil. When the flow was 600–1300 L/h, the average COD of the final effluent was 329 mg/L with an oil removal efficiency of 93.52%. In addition, the AID technology achieved the environmental protection goal with advantages of zero chemical consumption and simplified treatment process, thus providing a cleaner alternative for oily wastewater treatment. Graphical abstract: Aggregation-induced demulsification technology consisting of multi-stage packed beds filled with polyurethane sponge was developed, and the system was employed to recover oil from oily wastewater produced in petroleum industry. Image 1 Highlights: Aggregation-induced demulsification (AID) was proposed for oil-water separation. Demulsification was achieved by integrating polymer sponge with AID technology. Oil removal efficiency of AID system was more than 93%. Engineering parameters on the practical application of AID system were obtained. AID system exhibited excellent anti-fouling and cyclic performance.